In Silico Evaluation of Bisbenzylisoquinoline Compounds from Stephania sp. as EGFR Inhibitors for Triple-Negative Breast Cancer - Amanda Triastuti Amanda; Denny Satria (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Triple-negative breast cancer (TNBC) represents a highly aggressive breast malignancy subtype characterized by constrained therapeutic alternatives and poor clinical outcomes. Since Epidermal Growth Factor Receptor (EGFR) is frequently overexpressed in TNBC, it remains a strategic molecular target for anticancer drug innovation. This study evaluates the inhibitory potential of bisbenzylisoquinoline (BBIQ) compounds from Stephania species against EGFR using an in silico framework. Molecular docking analysis revealed that isotrilobine possessed the highest binding affinity toward EGFR, achieving a docking score of -10.5 kcal/mol, indicating potent interactions within the active site. Molecular dynamics simulations over a 100 ns trajectory demonstrated that the EGFR-isotrilobine complex maintained structural stability throughout, as evidenced by RMSD values of 0.193-1.223 Å, RMSF of 1.5 ± 1.1 Å, radius of gyration (Rg) of 4.597-4.918 Å, and a solvent-accessible surface area (SASA) of 772.3 Å². Hydrogen bond analysis identified an average of four stable interactions, reinforcing persistent ligand binding within the receptor pocket. Furthermore, MM-PBSA calculations yielded a binding free energy of 101.063 ± 127.26 kJ/mol, indicating energetically favorable binding. These findings suggest that isotrilobine and related BBIQ analogues exhibit significant potential as EGFR inhibitors for TNBC therapy, serving as viable candidates for further experimental validation and drug development.